Nomogram predicting the likelihood of live-birth rate after surgery for deep infiltrating endometriosis without bowel involvement in women who wish to conceive: A retrospective study. (April 2019) - Arfi, Alexandra; Bendifallah, Sofiane; Mathieu D'argent, Emmanuelle; Poupon, Clothilde; Ballester, Marcos; Cohen, Jonathan; Darai, Emile
Abstract: Objective: To study the fertility and live birth (LB) rate in women after surgery for deep infiltrating endometriosis (DIE) without bowel involvement and to evaluate the predictive factors of LB after DIE surgery without bowel involvement. Study design: Retrospective cohort study. A total of 118 women who wished to conceive and who underwent surgery for DIE without bowel involvement were analyzed between January 2006 and December 2014. A multivariate logistic regression analysis of selected factors and a nomogram to predict the subsequent LB rate was constructed. Results: Thirty-six woman had a LB (30.5%). In multivariate analysis, factors associated with a LB were: age ≤30 years (p = 0.0024), BMI ≤ 25 kg/m 2 (p = 0.029) and Enzian grade 1 (p < 0.001). These factors were associated to develop a nomogram. Before and after the bootstrap sampling procedure, the predictive model had an AUC of 0.84 (95% CI, 0.82–0.86) and 0.81 (95% CI, 0.79–83), respectively, and showed a good calibration. Conclusions: This work presents the originality of describing the fertility and the LB rate after surgery for DIE without bowel involvement with a predictive model. Such tools can help clinicians to support the patient in making an informed decision about fertility treatment options, contributing to the decision-making process by defining simple risk factors of poor LB probability that can help identify good candidates for MAR.